Er apostrofen et økologisk instrument? - Lind, Hans (Passage - Tidsskrift for litteratur og kritik, 2017)
Hans Lind: “The apostrophe – an ecological instrument?” This article investigates the relationship between the lyrical apostrophe and ecological thinking. Drawing on literary theories and ecological thinkers such as Jane Bennett and Timothy Morton, the article concludes that the apostrophe is related to the concept of ecological sensibility and is useful for communicating complex ecological ideas such as coexistence. These conclusions are based on an analysis of several poems containing apostrophes and a discussion of the role of poetry in soci ety and its ability to facilitate ecological thinking and awareness.